IMPLEMENTATION OF THE ROLE OF THE REGIONAL INSPECTORATE IN PREVENTING CORRUPTION IN MANDAILING NATAL REGENCY - Harahap, Latifah Angraini; Isnaini; Frensh, Wenggedes (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study aims to analyze the implementation of the role of the Regional Inspectorate in preventing corruption in Mandailing Natal Regency. The Regional Inspectorate has several main functions, such as internal supervision through audits, integrity development, and policy recommendations to improve the local government's financial management system. This study uses a qualitative method with data collection techniques in the form of interviews, observations, and documentation studies on the Inspectorate's supervision activities. The results of the study show that the Inspectorate plays an important role in preventing corruption, as seen from the increase in compliance of public officials and the decrease in budget irregularities by 40% in 2023. However, the Inspectorate faces major challenges, such as the limitation of competent human resources, political pressures that threaten independence, and budget and technology constraints. To overcome these obstacles, there needs to be a strengthening of human resources, the implementation of surveillance technology, and policies that ensure the independence of the Inspectorate. This study concludes that effective supervision, supported by independent policies and technology, is very influential in preventing corruption. These findings support the theory of internal oversight and public accountability, which emphasizes the importance of transparent and accountable oversight in preventing corruption in local government.